2011
DOI: 10.2217/nnm.10.133
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Administration of Photothermal Therapy and Chemotherapy to Cancer Cells Using Polypeptide-Based Degradable Plasmonic Matrices

Abstract: Aim Resistance of cancer cells to hyperthermic temperatures and spatial limitations of nanoparticle-induced hyperthermia necessitates the identification of effective combination treatments that can enhance the efficacy of this treatment. Here we show that novel polypeptide-based degradable plasmonic matrices can be employed for simultaneous administration of hyperthermia and chemotherapeutic drugs as an effective combination treatment that can overcome cancer cell resistance to hyperthermia. Method Novel gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 33 publications
2
53
0
1
Order By: Relevance
“…This difference in superficial charge can be attributed to the presence of MB on the surface of the nanoparticle. Similar work has been reported in literature where MB is encapsulated in PLGA using different encapsulation methods, and sizes range from 190 to 220 nm, with zeta potentials ranging between -38 mV and -17.5 mV [3]. When encapsulating 2.5% TDL, authors have obtained 220 to 266 nm diameters with PDI values of 0.19 and 0.4 [1].…”
supporting
confidence: 83%
“…This difference in superficial charge can be attributed to the presence of MB on the surface of the nanoparticle. Similar work has been reported in literature where MB is encapsulated in PLGA using different encapsulation methods, and sizes range from 190 to 220 nm, with zeta potentials ranging between -38 mV and -17.5 mV [3]. When encapsulating 2.5% TDL, authors have obtained 220 to 266 nm diameters with PDI values of 0.19 and 0.4 [1].…”
supporting
confidence: 83%
“…Thus, it appears that targeting Hsp90 may lead to new approaches to prevent and/or treat castration-resistant prostate cancer (115). Alternatively, co-administration of hyperthermia and 17-AAG released from plasmonic matrices was a powerful approach for the ablation of malignant cells and can be used in the form of similar combinations of nanoparticles and chemotherapeutic drugs for a variety of malignancies (116). For the complete list of breast, ovarian and prostate cancer cell response to combination of Hsp90 inhibitor and another therapy (treatment) in vitro and/or in vivo see Table IV.…”
Section: Combination Of Hsp90 Inhibitor With Second Therapymentioning
confidence: 99%
“…53,56 This aids in overcoming any potential hyperthermic resistance that may exist in various cancer subtypes. [57][58][59] However, to effectively utilize this combination therapy, the nanoparticles need to successfully penetrate into the core of the tumor embolic structures that exist in IBC. This study found that for SUM149 and rSUM149 cell lines, nanoparticles were homogenously distributed throughout the tumor embolic structure, as confirmed by MPM and histopathological staining.…”
mentioning
confidence: 99%